Carcinoid tumor and papillary thyroid carcinoma arising from ovarian mature cystic teratoma: two cases of an extraordinary malignant transformation - Billod, Jimmy A.; Saure, Joella G.; Natavio, Katrina Mae A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The most common malignant transformation of mature cystic teratoma of the ovary (MCTO) is squamous cell carcinoma, whereas, carcinoid tumor and papillary thyroid carcinoma are extremely extraordinary. This paper presents two rare cases of malignant transformation from MCTO. First, in a 33 year old, nulligravid, who underwent oophorocystectomy for a dermoid cyst. Histopathologic and Immunohistochemical studies revealed a carcinoid tumor arising from a mature cystic teratoma. Second, in a 52 year old who underwent, total abdominal hysterectomy with bilateral salpingo-oophorectomy for an ovarian new growth, with a final histopathologic and immunohistochemical analysis showed follicular variant of papillary carcinoma arising from mature cystic teratoma. Preoperative diagnosis of MCTO can be made through physical examination and imaging however not the concealed malignancy. Thorough extensive sampling and histopathologic examination of a dermoid cyst is necessary to detect malignant transformation. The optimal management of the disease is uncertain because of its rarity, but complete excision of tumor renders excellent prognosis.